Upaya Meningkatkan Keterampilan Motorik Halus Melalui Kegiatan Melipat Kertas Pada Anak Didik Kelompok B Semester Gasal TK Pertiwi Kacangan Kecamatan Todanan Kabupaten Blora Tahun Pelajaran 2015/2016 - SUKIRNO, SUKIRNO, Drs. Sutan Syahrir Zabda, SH,MH (2015)
Motorik's skill child fine group B at undeveloped TK Pertiwi Kacangan with every consideration. This research intent to increase motorik's skill child fine via activity folds paper. This research constitute Action Research Brazes. Subjek is research is 20 agglomerate childs B. this observational Object is motorik's skill fine by use of model Kemmis and Mc Taggart. Data collecting tech at do by use of observation and documentation. Tool that is utilized is observation instrumental sheet for child and estimation sheet to learn. Analisis's tech data was done by descriptive quantitative. Specified success indicator which is 75% of 20 child has motorik's skills fine. This research is done in two cycles. The result of observationaling to point out that motorik's skill child fine group B on pre action phase as much 20%, on cycle 1 as much 60%, and on cycle 2 as much 80%. Prosentase'sacquisition on cycle 2 proves that this research have reached success indicator, which is skill motorik is child fine experience step-up 80%. Observational steps that can increase motorik's skill fine did by activity folds paper, by use of paper media that its greater measure of paper that utilized by child. Base observational result gets to be concluded that passes through activity to fold paper can increase motorik's skill fine on agglomerate child b at TK Pertiwi Kacangan Todanan's district Blora's Regency.